Maximum Principles of Nonhomogeneous Subelliptic p-Laplace Equations and Applications (Journal of Partial Differential Equations, 2020)
Maximum principles for weak solutions of nonhomogeneous subelliptic p-Laplace equations related to smooth vector fields {X_j} satisfying the Hömander condition are proved by the choice of suitable test functions and the adaption of the classical Moser iteration method. Some applications are given in this paper.
Keywords: Subelliptic p-Laplacian; maximum principle; Harnack inequality